Falungong - Religion, Sekte oder Kult? Eine Heilsgmeinschaft als Manifestation von Modernisierungsproblemen und sozialen Entfremdungsprozessen - Thomas Heberer (Gerhard-Mercator-Universität Duisburg, Institut für Ostasienwissenschaften, 2001)
This paper discusses the ideological contents, and the social background of Falungong, a sect suppressed and persecuted by the Chinese state since several years. It focuses not on violations of human rights and torture of sect members, but tries to identify the character and features of Falungong. Therefore, it particularly analyses the teachings of Li Hongzhi, its founder and master. Moreover, sects like Falungong and their suppression have to be comprehended from a historical perspective that suppressed religion and religious movements in the case that they challenged the state. The problems that arose during the processes of modernization and social change and the reaction from parts of the population (e.g. religious revival) have to be understand in the context of developments in recent years.
Keywords: 330; Sekten; Kulte; Religion; Qigong; Modernisierungsprozesse